Molecular identification of Plasmodium spp. and blood meal sources of anophelines in environmental reserves on São Luís Island, state of Maranhão, Brazil - Figueiredo, Mayra Araguaia Pereira [UNESP]; Di Santi, Silvia Maria; Manrique, Wilson Gómez; Gonçalves, Luiz Ricardo [UNESP]; André, Marcos Rogério [UNESP]; MacHado, Rosangela Zacarias [UNESP] (Springer Nature, 2017)
Background: Considering the diversity of feeding habits that females of some species of anophelines present, it is important to understand which vertebrates are part of blood food sources and how important is the role of each in the ecoepidemiology of malaria. There are many vector species for Plasmodium spp. in the State of Maranhão, Brazil. In São Luís Island, Anopheles aquasalis is the main vector for human malaria; this species is abundant in areas with primates that are positive for Plasmodium. Anopheles aquasalis has natural exophilic and zoophilic feeding behavior, but in cases of high density and absence of animals, presents quite varied behavior, and feeds on human blood. In this context, the objective of the present study was to identify Plasmodium spp. and the blood meal sources of anophelines in two environmental reserves on São Luís Island, state of Maranhão, using molecular methods. Methods: Between June and July 2013, female anophelines were collected in the Sítio Aguahy Private Reserve, in the municipality of São José de Ribamar, and in the Sítio Mangalho Reserve, located within the Maracanã Environmental Protection Area, in the municipality of São Luís. CDC-type light traps, Shannon traps and protected human bait were used during three consecutive hours in peridomestic and wooded areas. Pools of anophelines were formed using mosquitoes of the same species that had been caught at the same site on the same date. A genus-specific amplification protocol based on the 18S rRNA gene was used for qPCR and cPCR. Results: A total of 416 anophelines were collected, of the following species: An. aquasalis (399), An. mediopunctatus (3), An. shannoni (1), An. nuneztovari (sensu lato) (1), An. goeldii (1), An. evansae (2) and An. (Nyssorhynchus) sp. (9), comprising 54 pools. Two pools were positive for Plasmodium (2/54) based on the 18S rRNA gene. In the phylogenetic analysis using the maximum likelihood method, based on a 240 bp fragment of the 18S rRNA gene, it was found that the sequences of Plasmodium sp. amplified from pools of An. aquasalis (pool 2) and An. nuneztovari (s.l.) (pool 10) were phylogenetically related to a clade of P. falciparum isolates from India, and to a clade of Plasmodium sp. isolates from psittacines in Brazil, respectively. Cat, dog and human DNA were identified in the blood meals of the anophelines sampled. Conclusion: The species An. aquasalis was the most abundant anopheline species in São Luís Island. Plasmodium spp. DNA was detected, thus confirming the importance of this species as the main vector on São Luís Island, Brazil. In addition, the presence of An. nuneztovari (s.l.) with DNA positive for Plasmodium spp. confirms its importance as a secondary vector.
Keywords: Anopheles; Feeding habit; Malaria; PCR; Vector